2017
DOI: 10.3390/ijerph14030220
|View full text |Cite
|
Sign up to set email alerts
|

Influencing Factors of the Body Mass Index of Elementary Students in Southern Taiwan

Abstract: The body mass index (BMI) of school children in Taiwan is markedly increasing. According to statistical data from the Taiwan Ministry of Education, the prevalence of obesity in school children from the southern part of the country is the highest in Taiwan. Thus, exploring the factors influencing BMI in elementary school children from southern Taiwan is crucial. This study investigated the influencing factors including physical activity levels, sedentary behaviors, dietary habits, and perceived body shape on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 28 publications
1
8
0
2
Order By: Relevance
“…Sample sizes of included studies ranged from 91 to 24,800 (median: 938), and half of studies were conducted in Canada (n=7) or the US (n=6). The youngest age range included was 2-13 years [29], as most focused on the 10-12 year old age range [28,30,36,[45][46][47]49] or included a broad age range of adolescents ages 11-18 years old [20,26,27,32,37,39,42]. The oldest data were collected in 2001 [35], and the most recent data collection was 2015 [48], with all other studies occurring between these time points.…”
Section: Results-mentioning
confidence: 99%
See 1 more Smart Citation
“…Sample sizes of included studies ranged from 91 to 24,800 (median: 938), and half of studies were conducted in Canada (n=7) or the US (n=6). The youngest age range included was 2-13 years [29], as most focused on the 10-12 year old age range [28,30,36,[45][46][47]49] or included a broad age range of adolescents ages 11-18 years old [20,26,27,32,37,39,42]. The oldest data were collected in 2001 [35], and the most recent data collection was 2015 [48], with all other studies occurring between these time points.…”
Section: Results-mentioning
confidence: 99%
“…There were patterns distinguishing the articles that did or did not observe a significant association of video game play with obesity. Articles that found a positive association between video game play and obesity typically collected data after 2012 [20,[45][46][47][48][49] except for one where data were collected in 2009 [39,40]. Articles reporting a positive association also typically combined video games with other screen devices (namely mobile phones and computer use), making it difficult to parse out the independent relationship of video game play and obesity aside from these other types of screen-time [47,48].…”
Section: Results-mentioning
confidence: 99%
“…Video games are especially attractive to children. Unfortunately, numerous studies have demonstrated that overweight and obesity may be attributable to a long time spent playing video games [4][5][6][7][8][9]. An advantageous alternative to conventional computer games is offered by active video games (AVGs), sometimes called exergames.…”
Section: Introductionmentioning
confidence: 99%
“…In Taiwan, the availability of a high-fat and high-energy diet has steadily risen in recent years (Chou and Chen, 2017). The obesity problem has become an important public health issue.…”
Section: Introductionmentioning
confidence: 99%
“…The obesity problem has become an important public health issue. The prevalence of obesity was 29.72% in school children (Chou and Chen, 2017), and overweight and obese children are likely to stay obese into adulthood (Bray, 1996). The World Health Organization (WHO) classified obesity as a chronic disease.…”
Section: Introductionmentioning
confidence: 99%